حكم أخذ الزكاة من غير نية صاحب المال:دراسة فقهية مقارنة بالقانون الباكستاني: The Ruling on taking Zakāt without the Owner’s Intention: A Comparative Analysis of Islamic Law and Pakistani Law (Al Basirah, 2025)
This research examines the jurisprudential and legal perspectives on the issue of the ruler’s compulsory collection of zakat without the payer’s intention, with a specific focus on the application of Pakistani law. The study aims to determine whether such compelled collection fulfills the religious obligation of zakat both outwardly and inwardly. Employing an inductive, analytical, and comparative methodology. The research gathers textual evidence from the Quran, Sunnah, and other sources of Islamic law, alongside statutory provisions of the Zakat and Ushr Ordinance, 1980 in Pakistan. Jurists have differed on this matter: the majority of Hanfi, Maliki, Shafi, and Hanbali scholars hold that compulsory collection by the ruler fulfills the obligation outwardly and inwardly; some Shafi’i and Hanbali scholars, including Ibn Taymiyyah and Ibn ‘Uthaymeen, maintain that it is valid outwardly only; while a minority opinion among the Hanafi school of thought states that it does not suffice without the payer’s intention. The legal framework in Pakistan mandates compulsory deduction of zakat from certain assets, particularly bank deposits, without requiring the payer’s intention, and treats such deductions as full discharge of the obligation, with limited exceptions. The findings indicate that Pakistani law aligns closely with the majority juristic view, though it emphasizes the administrative and regulatory nature of zakat collection more than its devotional aspect. The study concludes that while the compulsory system achieves the socio-economic objectives of zakat, its disregard for the payer’s intention raises theological considerations regarding personal worship and sincerity.Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified.Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies.Participant Consent:  The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.Data Fabrication/Falsification Statement: The author(s) declare that no data have been fabricated, falsified, or manipulated in this study.Copyright: Author(s) retains the Copyright of this article.
Keywords: Pakistani Law; Zakat and Ushr Ordinance, 1980; Zakat; Compulsory Collection; Intention; Islamic Jurisprudence